Up-Regulation of Cluster of Differentiation (CD) 11b Expression on the Surface of Canine Granulocytes with Human Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) - NAKAGAKI, Kazuhide; NUNOMURA, Yuka; UCHIDA, Kanji; NAKATA, Koh; TAZAWA, Ryushi (Journal of Veterinary Medical Science, 2014)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a pleiotropic cytokine, sharing a common beta subunit (CDw131) with interleukins 3 and 5. GM-CSF is important for its direct and indirect involvement in host defense. In veterinary medicine, human (h) GM-CSF has been used as a substitute for canine GM-CSF to stimulate canine granulocytes and macrophages. In this study, we compared the effects of three distinct hGM-CSFs produced by bacteria, yeasts and Chinese hamster ovary (CHO) cells with those of Escherichia (E) coli-produced canine GM-CSF on the cluster of differentiation 11b (CD11b) expression in canine granulocytes. The median effective dose (ED50) of hGM-CSFs from bacteria, yeasts and CHO cells was 3.09, 4.09 and 4.27 ng/ml, respectively, with no significant difference among three. In contrast, a significant difference was observed between ED50 of canine GM-CSF (0.56 ng/ml) and three hGM-CSFs according to the paired t-test (P<0.05). We conclude that hGM-CSF can activate canine granulocytes, but the average activity of the three rhGM-CSFs was approximately 15% of that of canine GM-CSF.